1992
DOI: 10.1002/pen.760321506
|View full text |Cite
|
Sign up to set email alerts
|

Optical waveguiding as a method for characterizing the effect of extended cure and moisture on polyimide films

Abstract: Integrated optics techniques (i.e., guiding light through a thin film) have been used to study the effects of extended cure and moisture exposure on polyimide films as manifested in changes in the TE (in-plane) and TM (out-of-plane) refractive indices and in their difference (birefringence). Mechanical testing of these films has been done using the load-deflection technique. Du Pont polyimide Pyralin 2555 and 2556 (benzophenone tetracarboxylic dianhydride-oxydianiline/metaphenylene diamine), cured repeatedly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Film thickness and refractive index were determined by a prism coupling method using a Metricon prism coupler. [ 12,13] In this method, shown schematically in Figure 4, a freestanding film is pressed against a high index prism using a piston with a curved surface. A thin silicon wafer may be placed between film and piston surface.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Film thickness and refractive index were determined by a prism coupling method using a Metricon prism coupler. [ 12,13] In this method, shown schematically in Figure 4, a freestanding film is pressed against a high index prism using a piston with a curved surface. A thin silicon wafer may be placed between film and piston surface.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…First, in most spin-cast polyimides, and in PMDA/ODA in particular, hydrodynamic forces and the presence of the substrate give rise to a net polymer chain alignment in the plane of the film. The existence of such ordering is inferred from significant differences between inand out-of-plane indices of refraction [9], [10], large differences between the in-and out-of-plane thermal expansion coefficients [11], anisotropy in fluid transport properties [12], [13], and, most directly, from x-ray diffraction measurements [14]- [17]. It has been suggested that in light of the anisotropy seen in other material parameters, the in-and out-of-plane moduli should be different.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer chains confined by a substrate are biaxially stretched during solvent evaporation, which preferentially aligns the chains to the in‐plane direction . Many studies on the degree of chain orientation in PI films have been conducted using birefringence, X‐ray diffraction, and polarized attenuated total reflectance (ATR)/Fourier transform infrared spectroscopy (FTIR) . In these experiments, the chain orientation of PI was associated with the physical and optical properties of a film such as CTE, elastic modulus, and refractive index .…”
Section: Introductionmentioning
confidence: 99%